2014
DOI: 10.1364/josab.31.002769
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Tamm states: dual enhancement of light inside the plasmonic waveguide

Abstract: A type of Tamm states inside metal-insulator-metal (MIM) waveguides is proposed. An impedance based transfer matrix method is adopted to study and optimize it. With the participation of the plasmonic Tamm states, fields could be enhanced twice: the first is due to the coupling between a normal waveguide and a nanoscaled plasmonic waveguide and the second is due to the strong localization and field enhancement of Tamm states. As shown in our 2D coupling configuration, |E| 2 is enhanced up to 1050 times when 155… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…Then, the time-consuming FDTD calculation is performed to determine the best values of d 1 and d 2 around the values found by the TMM. It has been shown that the TMM results match well with full-wave simulations13. In our case, as shown in Fig.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Then, the time-consuming FDTD calculation is performed to determine the best values of d 1 and d 2 around the values found by the TMM. It has been shown that the TMM results match well with full-wave simulations13. In our case, as shown in Fig.…”
Section: Resultssupporting
confidence: 83%
“…It should be noted that small numbers of periods are not able to confine enough energy at the BR terminal, and long MIM waveguides will introduce more Ohmic loss13. In Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to note that the full-width at half-minima (FWHM) or linewidth of OTP resonance decreases as N and d m increase. This is primarily a consequence of overall increase in reflectivity of the Ag-DBR geometry resulting in improved finesse for Ag-DBR cavity [32,33]. Therefore, the reduction in linewidth with increase in DBR pairs indicates that Ag-DBR architecture, with more number of bilayers (N) or thicker metal layer, will provide a better platform for increasing the Q-factor of OTP mode.…”
Section: Theoretical Analysismentioning
confidence: 99%